Balance of payments statistics yearbook - international Monetary Fund. Statistics Department; International Monetary Fund (Washington, D.C International Monetary Fund (IMF), 1994)
"​The Balance of Payments Statistics (BOPS) Yearbook provides tables of data, featuring regional and world totals of balance of payments and IIP components and aggregates as well as detailed information in the form of analytical and standard component presentations for economies. It is compiled in accordance with the IMF’s Balance of Payments Manual (BPM6). The Balance of Payments Statistics Yearbook is usually published in December" http://www.imf.org/en/publications/balance-of-payments-statistics/issues/2016/12/31/balance-of-payments-statistics-yearbook-2014-41469
Also issued in DVD format (Rec, #22502) Issued in three parts in 2 volumes Numbering changed in 2003 Vol. 46- 47 and vol. 54-55 are not available at the library
Keywords: International Trade; INTERNATIONAL TRADE; BALANCE OF PAYMENTS; FINANCIAL STATISTICS; PERIODICALS; YEARBOOKS